Investigation of Features of Mass-Fragmentation of Some N-(N,N-diethylacetamidino)-O-alkylfluorophosphates and Related Alkylfluorophosphonates and their Detection by Liquid Chromatography-High Resolution Mass Spectrometry - A. V. Braun; I. V. Rybalchenko; V. N. Fateenkov; V. A. Yashkir (Вестник войск РХБ защиты)
The timely detection of violations of the Convention on the Prohibition of the Development, Production, Stockpiling  and Use of Chemical Weapons and on Their Destruction (CWC) requires reliable methods for detecting toxic chemicals  that can be used for chemical attacks. The purpose of this investigation is to estimate chromatographic and mass-spectral  characteristics of some toxic chemicals recently included into Schedule 1 of the Annex on Chemicals of the CWC,  in particular N-(N,N-diethylacetamidino)-methylfluorophosphonate (DEAMP), N-(N,N-diethylacetamidino)-O-methylfluorophosphate (DEAOMP) and N-(N,N-diethylacetamidino)-O-ethylfluorophosphate (DEAOEP) and the  improvement of the qualification of the Chemical Analytical Control Laboratory experts taking part in the OPCW  Proficiency Tests. Materials and methods. The technique of high efficient liquid chromatography coupled with tandem  high resolution mass spectrometry (LC-MS/HRMS) was used during the investigation. The results. The results of  optimization of conditions of mass-spectrometric detection, selection of optimal pairs of ion reactions and program of  gradient elution during separation of chemicals in reversed-phase liquid chromatography were presented. Presented  approach was tested in analysis of model aqueous samples; metrological parameters of detection of compounds  were estimated. Conclusion. It was shown during investigation that electrospray ionization mass-spectra of DEAMP,  DEAOMP and DEAOEP contain intensive peaks of protonated molecular ions, which after further fragmentation  produce characteristic product-ions used for identification and high sensitive detection of parent compounds by LC-MS/HRMS. Limits of detection of DEAMP, DEAOMP and DEAOEP were 1.0 ng/mL, 0.5 ng/mL and 0.5 ng/mL,  respectively